P301L tau expression affects glutamate release and clearance in the hippocampal trisynaptic pathway. (31st October 2014) - Hunsberger, Holly C.; Rudy, Carolyn C.; Batten, Seth R.; Gerhardt, Greg A.; Reed, Miranda N.
Abstract Individuals at risk of developing Alzheimer's disease (AD) often exhibit hippocampal hyperexcitability. A growing body of evidence suggests that perturbations in the glutamatergic tripartite synapse may underlie this hyperexcitability. Here, we used a tau mouse model of AD (rTg(TauP301L)4510) to examine the effects of tau pathology on hippocampal glutamate regulation. We found a 40% increase in hippocampal vesicular glutamate transporter, which packages glutamate into vesicles, and has previously been shown to influence glutamate release, and a 40% decrease in hippocampal glutamate transporter 1, the major glutamate transporter responsible for removing glutamate from the extracellular space. To determine whether these alterations affected glutamate regulation in vivo, we measured tonic glutamate levels, potassium‐evoked glutamate release, and glutamate uptake/clearance in the dentate gyrus, cornu ammonis 3(CA3), and cornu ammonis 1(CA1) regions of the hippocampus. P301L tau expression resulted in a 4‐ and 7‐fold increase in potassium‐evoked glutamate release in the dentate gyrus and CA3, respectively, and significantly decreased glutamate clearance in all three regions. Both release and clearance correlated with memory performance in the hippocampal‐dependent Barnes maze task. Alterations in mice expressing P301L were observed at a time when tau pathology was subtle and before readily detectable neuron loss. These data suggest novel mechanisms by which tau may mediate hyperexcitability. <boxed-text content-type="graphic" id="jnc12967-blkfxd-1001" position="anchor" orientation="portrait"> </boxed-text> Pre‐synaptic vesicular glutamate transporters (vGLUTs) package glutamate into vesicles before exocytosis into the synaptic cleft. Once in the extracellular space, glutamate acts on glutamate receptors. Glutamate is removed from the extracellular space by excitatory amino acid transporters, including GLT‐1, predominantly localized to glia. P301L tau expression increases vGLUT expression and glutamate release, while also decreasing GLT‐1 expression and glutamate clearance.